Relation Analysis of Sea Surface Temperature And Chlorophyll-a Againts Yellowfin (Thunnus albacares) Catch Using Aqua MODIS Satellite Image Data In West Coast Northern Sumatera - Lumbantobing, Surya Rejeki W; Sari, T. Ersti Yulika; ', Usman (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2015)
ABSTRACTThis study aimed to determine the relationship of sea surface temperatureand chlorophyll-a by catch yellowfin fishing in the Coast of Western NorthSumatera. This study conducted in the Archipelago Fishing Port Sibolga andcontinued with image interpretation in Regional Fisheries Laboratory Faculty ofFisheries and Marine Sciences University of Riau, Pekanbaru. This research usesAqua MODIS satellite imagery level 1b data with a spatial resolution 1km. Thisstudy was conducted using a survey to get the catch and fishing Yellowfinposition data from the Fishing Port Of Sibolga Archipelago. Spatial analysismethods are used to see the distribution of sea surface temperature andchlorophyll-a. In this study sea surface temperature more dominant fish catchyellowfin than chlorophyll-a. At sea surface temperature range of 27-290C andchlorophyll-a concentration range of 1,03-1,09 mg/m3 dominant in January,yellowfin caught more fish with 221,773 tons while the dominant sea surfacetemperature 30-320C and chlorophyll-a concentrations 1,25-1.41 mg/m3 inDecember yellowfin caught fish less of 2,892 tons.Key Words : Sea Surface Temperature, Chlorophyll-A, Satelite Imagery, AquaMODIS, Thunnus albacares.